A case report PENATALAKSANAAN PASIEN PEREMPUAN USIA 72 TAHUN DENGAN ANEMIA PADA PENYAKIT GINJAL KRONIS MELALUI PENDEKATAN KEDOKTERAN KELUARGA DI PUSKESMAS KEDATON - Salsabila, Hasri Aghnia; Angraini, Dian Isti (CV. Jasa Sukses Abadi, 2024)
Anemia is a body condition characterized by a lower number of red blood cells or hemoglobin concentration than normal limits. According to WHO, 64 million or 23.9% of elderly suffer from anemia worldwide. One of the causes of anemia in the elderly is chronic kidney disease (CKD). According to RISKESDAS, the reported prevalence of CKD at ages ≥15 years is 0.38% in Indonesia with the highest incidence at ages 65-74 years. Appropriate holistic treatment using a family medicine approach is needed to improve the patient's quality of life. Implement comprehensive and holistic family doctor services by identifying risk factors, clinical problems, and patient management based on evidence-based medicine with strategies that are patient centered, family approach and community oriented. This study is a case report. Primary data was obtained through history taking, physical examination and home visits. Secondary data was obtained from patient medical records. Patient Mrs. T, 72 years old, has been diagnosed with anemia, complains of weakness accompanied by fatigue, dizzy eyes and unsteadiness when walking. An intervention was carried out in the form of providing health promotion using health posters regarding anemia in chronic kidney disease. The results of the intervention in patients obtained increased knowledge about the disease and compliance in maintaining health for successful therapy. Holistic management can improve the knowledge, attitudes and behavior of patients and families in maintaining health. Key words: Family Doctor, Anemia, Chronic Kidney Disease.